INVENTARISASI HAMA PASCAPANEN JAGUNG DALAM PENYIMPANAN DI TINGKAT PETANI DAN PEDAGANG DI KUPANG - Yustina Maria Silvia Wonga Puu; Samuel Pakan; Lince Makkun (Agriculture Faculty of Flores University, 2008)
This research was conducted at pest and plant disease laboratory, faculty of agriculture Nusa Cendana University in Kupang. Corn sample is taken from fanner in Amarasi, Kupang Timur, Kupang Barat and from the trader in Oesapa, Oesao, Penfui. This research intends to inventory pest after yields corn and to know the damage level of corn in farmer and trader. This research used a 32 kg corn sample for quotation methods. The observed variable is pest insect species, imago population, damage seed percentage, Weight decrease percentage, water level, temperature and moisturizer. Pest insect population and species observed on 1 kg corn. While seed damage and weight decrease per cent on 100 g corn seed and 5 g for water level. Data result tabulated and descriptively analyzed. The result of the research showed 1 pest insect species in the farmer corn storage is S.zeanmys and 2 species in trader corn storage is S.zeanmys and T confusum. Highest population S.zeamays founded in Penfui trader by 50,50/kg and lowest population 4,50/kg in farmer at Amarasi. T.confusum population only founded in trader not in farmer level. Highest population 2,17/kg in Penfui trader and lowest 0,17/kg in Oesapa trader. While highest seed damage percentage founded in Penfui trader by 11,13% and lowest 1,22% in farmer at Amarasi and highest weight decrease percentage founded in Oesapa trade by 0,77% and lowest 0,25% in farmer at Kupang Barat